2006
DOI: 10.1097/01.shk.0000223131.64512.7a
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Leukocyte Dysfunction Syndrome in Patients With Increasing Sepsis Severity

Abstract: Production of oxygen radicals is required for both microbicidal and tissue-toxic effector functions of granulocytes. Inasmuch as an ambivalent role of polymorphonuclear leukocytes (PMNs) may become apparent during sepsis, we studied levels of hydrogen peroxide (H2O2) production by PMNs depending upon the nature of different particulate and soluble stimuli in patients with increasing sepsis severity. Patients with sepsis (n = 15), severe sepsis (n = 12), or septic shock (n = 33) were prospectively enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 35 publications
5
72
1
1
Order By: Relevance
“…Similarly, in a rat model of peritonitis, neutrophils have been associated with liver failure (21). Recently, Kaufmann et al (15) reported neutrophil dysfunction in patients with severe sepsis (15). Neutrophils from severely septic patients exhibited a compromised phagocytic function; however, they produced higher amounts of ROS on activation by soluble stimuli (like fMLP, TNF-α, and TPA) compared with healthy subjects (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a rat model of peritonitis, neutrophils have been associated with liver failure (21). Recently, Kaufmann et al (15) reported neutrophil dysfunction in patients with severe sepsis (15). Neutrophils from severely septic patients exhibited a compromised phagocytic function; however, they produced higher amounts of ROS on activation by soluble stimuli (like fMLP, TNF-α, and TPA) compared with healthy subjects (15).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated low antioxidants and elevated levels of oxidative stress markers, such as lipid hydroperoxides and plasma nitrite, in septic patients (6,15). Recently, Kaufmann et al (12) reported neutrophil dysfunction in patients with severe sepsis. Neutrophils from patients with severe sepsis exhibited compromised phagocytic function; however, they produced higher amounts of ROS on activation by soluble stimuli (such as fMLP, TNF-α, and TPA) compared with healthy subjects (12).…”
mentioning
confidence: 99%
“…Recently, Kaufmann et al (12) reported neutrophil dysfunction in patients with severe sepsis. Neutrophils from patients with severe sepsis exhibited compromised phagocytic function; however, they produced higher amounts of ROS on activation by soluble stimuli (such as fMLP, TNF-α, and TPA) compared with healthy subjects (12). ROS/RNS can cause DNA-strand breakage, triggering the activation of poly(ADP-ribose) polymerase (PARP).…”
mentioning
confidence: 99%
“…4,5 The consequences of impaired immune function include enhanced susceptibility to nosocomial infection 6 or death from sepsis. 7 Neutrophils are the major front-line cellular defense against bacterial pathogens, and acquired defects in neutrophil function have been identified in both animal and human sepsis 8,9 as well as sterile SIRS. 10,11 However, the mediators driving these defects, and the mechanisms involved, remain uncertain.…”
Section: Introductionmentioning
confidence: 99%